Improving Firms' Innovation to Foster Productivity and Diversification : Competitive Reinforcement of Value Chains in Ecuador - Kim, Maria Deborah; Ferrer Morera, Gloria (World Bank, Washington, DC, 2017)
Over the last decade, Ecuador experienced inclusive growth fueled by a favorable external environment that financed a vast expansion of the public sector. The country is now facing severe external and fiscal challenges due to the significant extended fall in oil prices and the appreciation of the U.S. dollar. Since mid-2014, Ecuador has lost almost half of its merchandise export income due to the decline in oil prices. Oil revenues averaged 13.2 percent of GDP between 2011 and 2014 and one-third of total fiscal revenues. The fall in oil and other commodity prices on global markets has opened broad macroeconomic imbalances and exposed Ecuador's pre-existing vulnerabilities. As a fully dollarized economy with limited savings from the boom years, Ecuador cannot soften adjustment via a nominal depreciation or a drawdown of macroeconomic buffers. The strengthening of the U.S. dollar and the major currency depreciations in neighboring trading partners also place pressures on external competitiveness. Furthermore, access to foreign borrowing has become more limited. Consequently, the burden of the adjustment falls on fiscal and income policies.